Design Development of Rice Transplanter with Quality Function Deployment Method - Rozi Saferi; Asmara Yanto; Anton Bintarnel (Jurnal Teknik Mesin, 2022)
Today's agricultural development is inseparable from the development of agricultural tools and machinery technology. The application of this technology can be in the form of mechanization technology for rice cultivation using a rice transplanter. With the technology that helps them, it is hoped that agricultural productivity in Indonesia will increase from year to year and the farmers who are generally elderly can work more easily in managing their fields. The purpose of this study is to identify and determine the level of consumer needs related to rice transplanter, determine the technical characteristics of rice transplanter based on consumer preferences, and develop a House of Quality (HOQ) to determine the dominant design requirements and the priority technical characteristics of the equipment. Based on the House of Quality (HoQ) diagram, the best priority in improving the quality of products for making rice transplanter is an easy-to-use tool with a value of 138 with an average of 4.60. On the other hand, farmers also need a tool that can speed up rice planting on the condition that it is easy to use, because the suitability and convenience of rice farmers is a top priority. Furthermore, the design of the tool with a price that is not too expensive has a weight of 136 with an average of 4.53. This also shows that the price component is a priority for farmers to choose a rice transplanter.